If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -70 = 12x + 2 Reorder the terms: -70 + 4x = 12x + 2 Reorder the terms: -70 + 4x = 2 + 12x Solving -70 + 4x = 2 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -70 + 4x + -12x = 2 + 12x + -12x Combine like terms: 4x + -12x = -8x -70 + -8x = 2 + 12x + -12x Combine like terms: 12x + -12x = 0 -70 + -8x = 2 + 0 -70 + -8x = 2 Add '70' to each side of the equation. -70 + 70 + -8x = 2 + 70 Combine like terms: -70 + 70 = 0 0 + -8x = 2 + 70 -8x = 2 + 70 Combine like terms: 2 + 70 = 72 -8x = 72 Divide each side by '-8'. x = -9 Simplifying x = -9
| 6(3a+1)-30=3(20a-4) | | 16=(x+0.5)(x+0.5) | | 2h-35=12h-10h+15 | | 2x+7x+10=11x | | x+2+x+4+x^2-3x+3x-2=39 | | 12c^2-13c-35= | | 10x=9x-25 | | -9-6k+9-(2k)= | | .2m=22 | | -8h+3(1-5)=3b+37 | | 6(7y-5)=12y | | -(5a-4)+4a=5 | | 2c(9-5c)+6(c^2-c)=0 | | 3xy+x=8 | | 18x-2y+3-3x-3y= | | 4x+6+3=7 | | -(1+7x)+-6(-7+-x)=36 | | 9x^2-12y=15 | | 8h+3(1-5)=3b+37 | | 2x+5=7-4x | | 128v^2+448v+392=0 | | -10y+18=-3(5y-70)+5 | | 6x-3=27x-11 | | 2x+7x+10=x | | x^2+20x+12000=0 | | 12(x-2)=2(6x-3)-18 | | 10+h=54 | | -(3-2N)+7N=(N+3)3 | | -6(x-12)+2(x+2)=x-9 | | -6(6y+2)-(-5y-8)=2 | | 1.96=r^2+2r+1 | | -4+2n+16=n+7 |